Decoding climatic and tectonic signals in the Middle Pleistocene Ludwigshafen formation (Upper Rhine Graben) - Lukas Gegg; Philipp Stojakowits; Christian Hoselmann; Maria Knipping; Fiona Schwahn; Michael Weidenfeller; Ulrike Wielandt-Schuster; Frank Preusser (International Journal of Earth Sciences, 2026)

Ancient speleothem giant preserved in a high-Alpine cave (Dolomites, N Italy): Rare insights into the Neogene - Gabriella Koltai; Robert Scholger; Maria Knipping; Jian Wang; Hai Cheng; Silvia Frisia; Andrea Borsato; Denise Braunhofer; Christoph Spötl (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Terminal glacial overdeepenings: Patterns of erosion, infilling and new constraints on the glaciation history of Northern Switzerland - Marius W. Buechi; Angela Landgraf; Herfried Madritsch; Daniela Mueller; Maria Knipping; Franziska Nyffenegger; Frank Preusser; Sebastian Schaller; Michael Schnellmann; Gaudenz Deplazes (Quaternary Science Reviews, 2024)

The Hasli Formation of the Irchel Plateau – A key record for older Early Pleistocene interglacial sediments in northern Switzerland - Nigel Thew; Daniel Kälin; Gloria Cuenca-Bescós; Marius W. Buechi; Kirsty Penkman; Stephanie Scheidt; Maria Knipping; Fabian Maier; Isabel Urresti; Gaudenz Deplazes (Quaternary Science Reviews, 2024)

Rinikerfeld Palaeolake (Northern Switzerland) – a sedimentary archive of landscape and climate change during the penultimate glacial cycle - Lukas Gegg; Flavio S. Anselmetti; Gaudenz Deplazes; Maria Knipping; Herfried Madritsch; Daniela Mueller; Frank Preusser; Hendrik Vogel; Marius W. Buechi (Journal of Quaternary Science, 2023)
While timing and ice extent of the last glacial maximum are generally well known, the courses of earlier glaciations have remained poorly constrained, with one of the main reasons being the scarcity of sedimentary archives. This study introduces a new palaeolake record from a Mid‐Pleistocene glaciofluvial channel system in the Lower Aare Valley (Northern Switzerland). The record of Rinikerfeld comprises a >40 m long succession of Quaternary deposits that are targeted by multi‐method sedimentological analysis. Sedimentary facies together with geochemical and geotechnical parameters, pollen content, as well as luminescence ages allow the reconstruction of the establishment, evolution and infilling of the early Marine Isotope Stage 6‐aged Rinikerfeld Palaeolake. A drastic change in lake sediment composition and structure indicates cessation of the initial glacially derived input, which is explained by landscape modification and drainage rerouting during the Penultimate (Beringen) Glaciation. Geochemical and palynological data further reveal cold, initially periglacial but slightly ameliorating, climate conditions, while the lake was progressively filled up by local runoff, before being buried by periglacial colluvial diamicts, and potentially overridden by ice. It is therefore concluded that the onset of the Beringen Glaciation was an environmentally as well as geomorphically dynamic time period in the Northern Alpine Foreland.

Human induced landscape changes around Bafa Gölü (western Turkey) - Maria Knipping; Marc Müllenhoff; Helmut Brückner (Vegetation History and Archaeobotany, 2008)